(untitled) (Sebha University Conference Proceedings, 2025)
Controlling permanent magnet synchronous machines (PMSM) is particularly challenging due to their nonlinear dynamics. Traditional linear controllers, such as PI and PID, perform adequately in systems with constant parameters, but they often fall short when applied to nonlinear systems with variable parameters, lacking the necessary robustness. To address these limitations and achieve decoupled control of the machine, several methods have been proposed, with robust nonlinear control techniques gaining significant attention in power electronics and drive systems. Notable among these are sliding mode control (SMC) and nonlinear input output feedback linearization (IOFL). SMC is well-regarded for its exceptional dynamic performance in PMSM drives, offering high robustness and straight forward implementation in both software and hardware. However, its main limitation lies in the chattering phenomenon. In contrast, input-output linearization control demonstrates excellent behavior in both steady-state and dynamic regimes, while also providing effective decoupling of system variables. This article synthesizes two control approaches—sliding mode control and feedback linearization control based on input-output linearization—to regulate the speed of a PMSM. A comparative analysis conducted in Matlab/Simulink highlights the superior performance of the feedback linearization controller over SMC.